Effects of dietary fish oil on skeletal muscle vascular control in chronic heart failure rats: rest and exercise - Holdsworth, Clark T. (Kansas State University, 2013)
Impaired vasomotor control in chronic heart failure (CHF) limits the delivery of O[subscript]2 to skeletal muscle during exercise. Previous results demonstrate significant increases in skeletal muscle blood flow (BF) during exercise with omega-3 polyunsaturated fatty acid (PUFA) supplementation via fish oil (FO) versus safflower oil (SO) in healthy rats (Stebbins CL et al., Int J Sport Nutr Exerc Metab 20:475-86, 2010). Whether PUFA supplementation with FO will improve vasomotor control in CHF and skeletal muscle BF during exercise remains to be determined. This investigation tested the hypothesis that PUFA supplementation with FO would augment the skeletal muscle BF response to exercise in rats with CHF when compared to SO. CHF was induced in male Sprague-Dawley rats by myocardial infarction produced via left coronary artery ligation. Rats were then randomized to dietary FO (20% docosahexaenoic acid and 30% eicosapentaenoic acid, n = 8) or SO (5% safflower, n = 6) supplementation for 6 weeks. Rats remained on their respective diets until final experiments were conducted. Following acute instrumentation and recovery (> 1 hour), mean arterial pressure (MAP), skeletal muscle BF to the total hindlimb and individual muscles (via radiolabeled microspheres), and blood lactate concentration were determined during rest, submaximal treadmill exercise and exercise+LNAME (20 m · min[superscript]-[superscript]1, 5% incline). Left ventricular end-diastolic pressure (LVEDP) measured in the SO and FO groups during instrumentation were similar and demonstrated moderate CHF (LVEDP; SO: 14 ± 2; FO: 11 ± 1 mmHg, P>0.05). During submaximal exercise, MAP (SO: 128 ± 3; FO: 132 ± 3 mmHg) and blood lactate (SO: 3.8 ± 0.4; FO: 4.6 ± 0.5 mmol · l[superscript]-[superscript]1) were similar (P>0.05) between groups. Exercising hindlimb skeletal muscle BF was higher in SO compared to FO (SO: 120 ± 11; FO: 93 ± 4 ml · min[superscript]-[superscript]1 · 100 g[superscript]-[superscript]1). Specifically, 17 of 28 individual hindlimb muscle BF’s were higher (P<0.05) in SO. These data suggest that PUFA supplementation with FO in rats with moderate CHF decreases the skeletal muscle BF response to submaximal whole body exercise.
Keywords: Blood flow; Heart failure; Fish oil; Kinesiology (0575)